A study on the compressive mechanical properties of 316L diamond lattice structures manufactured by laser powder bed fusion based on actual relative density. (December 2022) - Liang, Zulei; Chen, Xiaolong; Sun, Zhonggang; Guo, Yanhua; Li, Yonghua; Chang, Hui; Zhou, Lian
Abstract: Lattice structure design is a novel structural lightweight method and has many advantages, but some researches ignored the effects of the factors studied on actual relative density and skipped actual relative density to discuss the effects on mechanical properties. In this paper, the effects of process parameters and geometrical parameters on the compressive mechanical properties of 316L diamond lattice structures manufactured by laser powder bed fusion were investigated on the basis of actual relative density. The results show that the actual relative density (28.0 % → 25.4 %) and the compressive strength in the building direction (55.7 ± 1.3 MPa → 42.0 ± 1.5 MPa) decrease as the hatch spacing (0.05 mm → 0.09 mm) increases, and they conform to the parabolic function relationship better than the Gibson-Ashby relationship, but the opposite in the XY direction. The actual relative densities and compressive strength inevitably conform to the Gibson-Ashby relationship regardless of the nominal relative densities and cell sizes, and the modulus (857 ± 54 MPa → 1019 ± 51 MPa) increases with the increasing of strut diameter (0.54 mm → 3.21 mm). The compressive strength could decrease slightly with the increasing of contour size (10 mm → 30 mm), while the modulus (964 MPa → 682 MPa) decreases rapidly. To sum up, the process parameters and geometrical parameters could affect the actual relative density significantly, and the actual relative density is the key to correctly analyze the effects of various parameters. The conclusions of this work are helpful to optimize the manufacturing process of lattice structures and design geometrical parameters according to the required performance.